Optimism and the SES Gradient in Adolescent Adiposity - Khullar, Dhruv (2011)
PURPOSE: To assess if dispositional optimism is associated with adiposity and explore if dispositional optimism mediates the relationship between parent education and adiposity (BMI z score). METHODS: Multivariable regression analyses of data collected from 1298 non-Hispanic black and white 12–19 year olds from a single Midwestern public school district. RESULTS: Less optimistic adolescents had higher BMI z scores (r = −0.09, p < 0.001). Addition of dispositional optimism to the regression model caused an approximately 10% attenuation of the parent education and BMI z score relationship. Sobel tests confirmed that this attenuation indicated partial mediation. CONCLUSION: Lower dispositional optimism is associated with higher adiposity and this association accounts for some of the influence of parent education on adolescent adiposity.